The Rupture of Young Muslim Intelligentsia in the Modernization of Indonesia - Yudi Latif (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
In March 1966, Army Chief of Staff Soeharto rose to power, taking control of the Indonesian Government. Soeharto's 'New Order' regime inherited a plethora of economic, political and social problems. The New Order came to the conclusion that these crises had evolved as a result of the previous regime's neglect of the economy and lack of concern for social welfare. Economic recovery was viewed as a priority by the new regime for it would tum the attention of the people from politics to the economy thus changing the national outlook from 'politik-sebagai-panglinta'(politics as commander) - as practiced during the Old Order - to 'ekonomi-sebagai-panglima' (economy as commander).DOI: 10.15408/sdi.v12i3.581